Hydrogen Sulfide Increases Production of NADPH Oxidase-Dependent Hydrogen Peroxide and Phospholipase D-Derived Phosphatidic Acid in Guard Cell Signaling. Issue 3 (2nd February 2018) - Scuffi, Denise; Nietzel, Thomas; Di Fino, Luciano M.; Meyer, Andreas J.; Lamattina, Lorenzo; Schwarzländer, Markus; Laxalt, Ana M.; García-Mata, Carlos
Abstract: Hydrogen sulfide (H2 S) is an important gaseous signaling molecule in plants that participates in stress responses and development. l -Cys desulfhydrase 1, one of the enzymatic sources of H2 S in plants, participates in abscisic acid-induced stomatal closure. We combined pharmacological and genetic approaches to elucidate the involvement of H2 S in stomatal closure and the interplay between H2 S and other second messengers of the guard cell signaling network, such as hydrogen peroxide (H2 O2 ) and phospholipase D (PLD)-derived phosphatidic acid in Arabidopsis ( Arabidopsis thaliana ). Both NADPH oxidase isoforms, respiratory burst oxidase homolog (RBOH)D and RBOHF, were required for H2 S-induced stomatal closure. In vivo imaging using the cytosolic ratiometric fluorescent biosensor roGFP2-Orp1 revealed that H2 S stimulates H2 O2 production in Arabidopsis guard cells. Additionally, we observed an interplay between H2 S and PLD activity in the regulation of reactive oxygen species production and stomatal movement. The PLDα1 and PLDδ isoforms were required for H2 S-induced stomatal closure, and most of the H2 S-dependent H2 O2 production required the activity of PLDα1. Finally, we showed that H2 S induced increases in the PLDδ-derived phosphatidic acid levels in guard cells. Our results revealed the involvement of H2 S in the signaling network that controls stomatal closure, and suggest that H2 S regulates NADPH oxidase and PLD activity in guard cells.